Diversidad, abundancia y conjuntos ictiofaunísticos del sistema lagunar-estuarino Chantuto-Panzacola, Chiapas, México - Díaz-Ruiz, Silvia (2004)
In the Chantuto-Panzacola system, Chiapas, México, a study of a fish community was carried out between March and November of 1997. From a total of 1 456 fish collected, 31 species, 25 genera and 19 families had been identified. The diversity and abundance were high in March with H’= 2.67 bits/ind, D = 3.89 sp/ind, biomass 1.88 g/m2, density 0.25 ind/m2 and average weight 7.55 g/ind. Significant differences were found between the ecological parameters and the environmental variables of the ecosystem in the months of study (ANOVA and Tukey, p<0.05). The multiple discriminant analysis showed that the temperature and the salinity was the most important factors in the variation of the community. The frequency analysis and spatial distribution of the fish allowed to define fish assemblages formed by several groups of species that inhabits the system. Nine dominant species were defined for the ecosystem, representing the 71% in number and the 76.4% in weight of the total catch, Achirus mazatlanus, Caranx hippos, Cathorops fuerthi, Centropomus robalito, Cichlasoma macracanthum, Cichlasoma trimaculatum, Gobiomorus maculatus, Gobionellus microdon and Lile gracilis.